A16 FIBER SUPPLEMENTATION DIFFERENTIALLY MODULATES RESPONSES TO FECAL MICROBIAL TRANSPLANTATION IN PATIENTS WITH METABOLIC SYNDROME AND SEVERE OBESITY: A RANDOMIZED, DOUBLE-BLIND, PLACEBO-CONTROLLED PILOT TRIAL. (4th March 2021) - Mocanu, V; Zhang, Z; Deehan, E; Samarasinghe, K; Hotte, N; Kao, D H; Karmali, S; Birch, D W; Walter, J; Madsen, K
Abstract: Background: Fecal microbial transplantation (FMT) from lean donors to obese patients with metabolic syndrome (MS) has been associated with promising yet short-term metabolic improvements. The concept of using dietary or fiber supplementation to enhance effects induced by FMT has been much discussed in the literature, but to date no human trials have examined this concept. Aims: The aim of this study was to determine if fiber supplementation following FMT was able to enhance or sustain FMT-mediated metabolic benefits. Methods: We performed a 12-wk double-blind randomized placebo-controlled trial in patients with severe obesity and MS recruited from Edmonton's Bariatric Clinic from 2018 to 2019. Patients were stratified by sex and block randomized 1:1:1:1 amongst one of four groups: (1) Placebo FMT and a non-fermentable fiber (NF) (2) Placebo FMT and fermentable fiber (FF); (3) FMT and non-fermentable fiber (FMT-NF); and (4) FMT and fermentable fiber (FMT-FF). Patients received a single dose of FMT (50g donor stool) with 20 oral capsules followed by a 6-wk period of daily fiber. The primary outcome was evaluating mean differences (MD) in insulin sensitivity from baseline to 6-wks using the homeostatic model assessment of insulin resistance (HOMA2-IR). Results: Sixty-eight patients were randomized with 61 completing the primary outcome (NF = 17; FF = 15; FMT-NF = 14; FMT-FF = 15) and evaluated using a modified intent-to-treat analysis. Baseline characteristics were similar with a mean BMI 45 ± 7 kg/m 2, a female predominance (83.6%), and a HOMA2-IR of 3.43 ± 2.2. There were no baseline differences in clinical characteristics, metabolic parameters, medications, or dietary intake. FMT-NF had improvements in HOMA2-IR (MD -24.0% ± 12.0%; p=0.02), insulin sensitivity (MD 27.6% ± 12.3%; p=0.02), and insulinemia (MD -25.4% ± 12.3%; p=0.02) from baseline to 6-wks (Figure 1). These benefits were associated with increased microbial richness and improvements in GLP-1 metabolism. Linear mixed model regression revealed that select bacterial taxa including Phascolarctobacterium, Ruminococcaeceae, and B. stercoris correlated with increased insulin sensitivity. Findings occurred in the absence of changes in anthropometric parameters, dietary intake, medication regimen and were not observed in groups receiving fermentable fiber or in any group following cessation of fiber. Conclusions: This proof-of-concept trial provides evidence that a single FMT dose combined with daily non-fermentable fiber supplementation can successfully improve insulin resistance in patients with metabolic syndrome and severe obesity on optimized medical therapy. Funding Agencies: W. Garfield Weston Foundation